Aerospace series. Steel FE-PM1802 (X5CrNiCu15-5). Consumable electrode remelted. Solution treated and precipitation treated. Forgings. a or D ≤ 200 mm. Rm ≥ 965 MPa. (9th October 2019) - British Standards Institution,
No abstract available